Representation of the Relationship Between Father and Son in the Picture Story Book Ayahku Seorang Nelayan by Zunda - Ivana Novelia; Suyatno (Raja Zulkarnain Education Foundation, 2026)
This research is predicated on the urgency of the “fatherless” phenomenon in Indonesia and the scarcity of children’s literature that comprehensively represents paternal emotional involvement. This study aims to elucidate the representation of the father-child relationship in the picture book Ayahku Seorang Nelaya by Zunda. The research employs a descriptive qualitative method utilizing a Children’s Literature criticism approach (Peter Hunt’s perspective), integrated with multimodal discourse analysis for visual elements and hermeneutics for textual elements. The findings demonstrate that the father figure is represented in a multidimensional and egalitarian manner. The findings include: (1) a high level of paternal involvement in the domestic sphere; (2) a relationship quality characterized by democratic interaction, communicative engagement, and emotional warmth; (3) parenting and education implemented through role modeling in daily activities integrated with nature; and (4) paternal roles and responsibilities that function not only as a breadwinner but are also fully engaged in fulfilling the child’s psychological and developmental needs. The conclusion asserts that this work presents an ideological construction offering a counter-narrative to the issue of father absence, rendering it relevant as an educational medium for the internalization of fatherhood values within the family.